What action should be taken by the private sector in job creation, trade expansion and foreign exchange generation?: a response from the small business sector - Goodwin, Bruce Haile (Dominica Association of Industry & Commerce RoseauDM, 1993)
Suggests that because of its natural characteristics, the small business sector can generate impressed positive action in relation to the three areas of the question. Concludes that in order to achieve this great impact the public and private sectors should work in close collaboration at all levels.